ANALISIS IMPLEMENTASI PERATURAN BUPATI PATI NOMOR 11 TAHUN 2020 TENTANG PERCEPATAN PENURUNAN STUNTING DI KABUPATEN PATI - Malinda, Aina Shinta; Maharani, Chatila (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
Pati, in. In Regency, 3,925 children will be affected by stunting in 2021, up from 3,997 in 2020. It has gone down, but not by much. A Pati Official Guideline was issued by the Pati local government to accelerate the reduction of obstructions in order to reduce obstruction rates until the objective is reached in 2023. This study aims to find out how Pati Regency's Regent Regulation number 11 of 2020, which aims to reduce stunting more quickly, will be implemented. The research employs a qualitative methodology. Participants in this study included nutrition officers at the. Sukolilo. I.and. data are gathered through in-depth interviews, observation, and documentation by the Head of the Human Development Division at Bapeeda, the Head of the Public Health Division at the Health Service, mothers of stunted toddlers in the two puskesmas areas, and Pati II health centers. This study demonstrates that the rule the district head issued to speed up the reduction of stunting in Pati Regency is working. There are satisfactory categories for communication, resources, attitude, and the structure of the bureaucracy. There is still a lack of community support for the environment.